FEMALE PSEUDO HERMAPHRODITISM: LATE ONSET CONGENITAL ADRENAL HYPERPLASIA - Akhtar, Nosheen; Hayat, Zartaj; Bari, Arifa (Journal of Ayub Medical College Abbottabad, 2018)
Non-classic congenital adrenal hyperplasia is a genetic condition caused by deficiency of 21-hydroxylase deficiency (NCAH). It is a milder and later onset form of a genetic condition known as congenital adrenal hyperplasia. We present four cases of non-classical congenital adrenal hyperplasia presented in gynae OPD foundation university medical college Fauji foundation hospital from Jan 2016 to March 2017. The presenting complaints were hirsuitim, menstrual problem and virilization of genitalia. Two girls were having primary amenorrhea while rests of two were having secondary amenorrhea. Two patients were already diagnosed as non-classical congenital adrenal hyperplasia due to ambiguous genitalia at the time of birth while the rest of two with marked clitoromegaly were diagnosed during workup in gynae OPD. Menarche was achieved successfully among those with primary amenorrhea after treatment. All four girls were referred to plastic surgery for clitoral reduction surgery. The post-surgery patient satisfaction level was high. Correct diagnosis of the disease can cure the patient instead of letting her live a life of being labeled with social stigmata of an intersex individual. Keywords: Non-classical congenital adrenal hyperplasia; hirsuitism; Clitoromegaly